RECURRENT MILD TRAUMATIC BRAIN INJURY AMONGST A COHORT OF RUGBY UNION PLAYERS. Issue 7 (11th March 2014) - Hollis, S; Heller, G; Stevenson, M; Schofield, P
Abstract : Background: Community, or non-professional, rugby has a high incidence of mild traumatic brain injury (mTBI). Risk of further mTBI, or long term consequences of repeat mTBI, is an emerging public health issue. Objective: To identify the time to recurrent mTBI and key predictors for time to recurrent mTBI among community rugby players. Design: Prospective cohort study. Setting: Rugby union players from Sydney, Australia playing in grade, suburban and school-level community competitions. Participants: A cohort of 3 207 male players was recruited pre-season and followed between one and three playing seasons. Demographic information, player characteristics and concussion history was collected. Players sustaining an mTBI were recorded and information pertaining to the injury, recovery and return-to-play was collected over three months. Risk factor assessment: Loss of consciousness and post-traumatic amnesia. Main outcome measurements: Time to mTBI, namely, the number of hours of game exposure played up to the time the player sustained a first and repeat mTBI. Results: Players were more likely to sustain a second mTBI if they experienced loss of consciousness (LOC) or post-traumatic amnesia (PTA) with their first mTBI. Players who experienced LOC with their first mTBI were three times more likely to sustain a second mTBI compared to those who did not experience LOC (P=.037). Players who experienced PTA with their first mTBI were 2.5 times more likely to sustain a second mTBI compared to those who did not experience PTA (P=.059). Conclusions: Community rugby players are three times more likely to sustain a subsequent mTBI if they experienced a LOC with their first mTBI, and 2.5 times more likely if they experienced PTA. It is recommended that coaches and support staff identify players who experience LOC or PTA with their mTBI in order to prevent or delay subsequent mTBIs from being sustained by the player.